2002
DOI: 10.1046/j.1432-1033.2002.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of palytoxin on apical H+/K+‐ATPase in rat colon

Abstract: Palytoxin stimulated a cation-dependent short-circuit current (Isc) in rat distal and proximal colon in a concentration-dependent fashion when applied to the mucosal surface of the tissue. The distal colon exhibited a higher sensitivity to the toxin. The palytoxin-induced Isc was blocked by vanadate but was resistant to ouabain or scilliroside, suggesting the conversion of a vanadate-sensitive H + /K + -ATPase into an electrogenic cation transporter. Cation substitution experiments with basolaterally depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…There is controversy regarding its pharmacological sensitivity to ouabain (Codina et al 1996;Cougnon et al 1996;Cougnon et al 1998;Sangan et al 2000) and this complicates the interpretation of experiments in which both PTX and ouabain are present. It has been reported that PTX has an effect on both distal and proximal colon, and it has been suggested that this action of PTX is mediated by interaction with ngH,K-ATPase (Scheiner-Bobis et al 2002). However, since the conductance increase produced by PTX action on the Na,K-ATPase is so large, the presence of only a small amount of Na, K-ATPase in distal and proximal colon would be sufficient to explain the results obtained in those tissues.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is controversy regarding its pharmacological sensitivity to ouabain (Codina et al 1996;Cougnon et al 1996;Cougnon et al 1998;Sangan et al 2000) and this complicates the interpretation of experiments in which both PTX and ouabain are present. It has been reported that PTX has an effect on both distal and proximal colon, and it has been suggested that this action of PTX is mediated by interaction with ngH,K-ATPase (Scheiner-Bobis et al 2002). However, since the conductance increase produced by PTX action on the Na,K-ATPase is so large, the presence of only a small amount of Na, K-ATPase in distal and proximal colon would be sufficient to explain the results obtained in those tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Reports on the effect of palytoxin on the apical versus basolateral side of polarized epithelial cells from kidney (LLC-PK1), provide additional evidence that the site of palytoxin action is the Na,K-ATPase (Mullin, et al 1991). However, it has been reported that palytoxin acts on both distal and proximal parts of the descending colon (Scheiner-Bobis, et al, 2002). Extensive pharmacological characterizations of colonic and other H,K-ATPases found in collecting duct have yielded conflicting conclusions regarding its sensitivity to ouabain (Codina J., et al, 1996;Cougnon, et al, 1996;Del Castillo, et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that palytoxin interferes with both the Na ϩ -K ϩ pump and the SERCA might be explained by structural similarities and the high degree of homology between the two ion pumps (48). In line with this notion, Scheiner-Bobis et al (45) suggested in a recent report that palytoxin can convert the colonic H ϩ -K ϩ pump, another closely related P-type ion pump, into a cation channel. While our experiments on isolated SR vesicles clearly establish an inhibitory action of palytoxin on the SERCA, they do not provide any insights into the mechanism of inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…4 These drugs stimulate cation-dependent short-circuit currents in the colonic mucosa, possibly by converting the vanadate-sensitive H+/K+-ATPase into an electrogenic cation transporter. 5 Should the demand for energy from ATP (adenosine triphosphate) hydrolysis so induced exceed the capacity for ATP resynthesis, the action might precipitate an aerobic energy deficit or unreversed ATP hydrolysis similar to that developing for different reasons in ischemic colitis that occurs as a complication of abdominal aortic surgery. As in C. difficile colitis, the passage of liquid, bloodstained stools is an established feature of this condition.…”
Section: Margaret Somervillementioning
confidence: 99%